Religious behaviour, labour supply, and social conformity: Evidence from a ban on Muslim religious veiling - Kevin Devereux; Blair Long; Margaret Samahita (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2026)
In 2019 Canada's second-largest province introduced a selective ban on religious clothing in the public service as part of a broader effort to promote secularism in the public sphere. Using novel survey data we find evidence of spillovers onto labour force participation and religious expression among those outside the public service. We study the largest legally targeted group: Muslim women. Conducting a difference-in-difference analysis comparing Muslim women in Quebec to those in the rest of Canada, we find a relative reduction in the most liminal religious behaviour - wearing a veil in public - among both Canadian-born Muslim women and immigrants. We also find a relative increase in labour force participation among Canadian-born Muslim women, but not among immigrants. We corroborate the employment results using high quality administrative tax records, and document an anticipation effect: Muslim women sort into the targeted occupations in the year before implementation. The results are consistent with social norm signaling influencing private religious behaviour and labour market outcomes.
Keywords: 330